Toward system-level understanding of baculovirus–host cell interactions: from molecular fundamental studies to large-scale proteomics approaches - Monteiro, Francisca; Carinhas, Nuno; Carrondo, Manuel J.; Bernal, Vicente; Alves, Paula M. (Frontiers in Microbiology, 2012)
Baculoviruses are insect viruses extensively exploited as eukaryotic protein expression vectors. Molecular biology studies have provided exciting discoveries on virus-host interactions, but the application of omic high throughput techniques on the baculovirus-insect cell system has been hampered by the lack of host genome sequencing. While a broader, systems level analysis of biological responses to infection is urgently needed, recent advances on proteomic studies have yielded new insights on the impact of infection on the host cell. These works are reviewed and critically assessed in the light of current biological knowledge of the molecular biology of baculoviruses and insect cells.